Dyslipidemia in Patients with a Cardiovascular Risk and Disease at the University Teaching Hospital of Yaoundé, Cameroon - Vicky Jocelyne Ama Moor; Sylvie Ndongo Amougou; Sebastien Ombotto; Felicien Ntone; Doriane Edna Wouamba; Bernadette Ngo Nonga (International Journal of Vascular Medicine)
Objective. To determine the frequency of lipid abnormalities in patients with a cardiovascular risk and disease at the University Teaching Hospital (UTH) of Yaoundé. Materials and Methods. We conducted a cross-sectional study from 1 March to 31 May 2015 at the UTH of Yaoundé. We included all patients seen in the outpatient department with a diagnosis of a cardiovascular disease or a risk factor for cardiovascular disease. Patients who accepted to participate in the study were asked to answer a questionnaire; after that a blood sample was taken for lipid profile. An informed consent was signed by all the participants and the study has received approval from the national ethic committee. Results. We recruited 264 patients of which 119 were men and 145 were women with a sex ratio of 0.82. Mean age was 61.36 years. The frequency of lipid profiles abnormalities was as follows: low HDL cholesterol (44.3%), hypertriglyceridemia (18.9%), high LDL cholesterol (3.8%), and high total cholesterol 3.4%). Hypertriglyceridemia was strongly associated with type 2 diabetes mellitus. Conclusion. Low levels of HDL cholesterol and hypertriglyceridemia are more prevalent in our study population. More studies are needed to confirm this finding in our environment.